Voice in the lyric singers. Protocol for clinical and acoustic assessment - Fernández Gutiérrez, María José; Isidoro Álvarez, Carla; Rodríguez, Paloma Sirgo; Núñez Batalla, Faustino; Álvarez Marcos, César Antonio (Revista de Investigación en Logopedia, 2021)
The goal of this study is to develop a clinical and acoustic protocol with several techniques to evaluate lyrical singers voice. 18 lyrical singers, considered themselves as healthy, were selected including soprano, mezzo-soprano, contralto, tenor, baritone and bass. All of them were submitted to anamnesis, S-VHI and to a series of aerodynamics (TMF, index s/e and phonation quotient) and acoustic (F0, intensity, HNR, Jitter, Shimmer, spectrogram, phoneme and LTAS) studies, as well as to a clinical exploration and stroboscopic instrumentation. 33% were smokers, this habit being more frequent in men. By means of S-VHI, 20 points out of 144 possible were detected, a relatively high score about their degree of disability. Almost half of them obtained values in the TMF , index s/e and phonation quotient within the normal range. In most cases, the acoustics characteristics and vocal and dynamic ranges were within normal limits. In 55%, some type of laryngeal pathology was observed. In order to detect unnoticed laryngeal pathologies singers should avoid the use of tobacco, and be checked periodically by doctors. The aerodynamic and acoustic values show alterations with respect to normal reference values. The presence of vibrato and formant of the singer can be seen by means of the spectrogram, as well as and the LAST, as well as vocal and dynamic ranges is seen with the phonogram. Use of the clinical and acoustic protocol provides important information to complete that obtained by the vocal therapist or technique teacher in the perceptual analysis of the professional voice.